The Correlation Between Migraine and Patent Foramen Ovale - Liu, Kaiming; Wang, Brian Z.; Hao, Yishu; Song, Shuijiang; Pan, Mengxiong (Frontiers in Neurology, 2020)
Background: Migraine is a widespread neurological disorder. The patent foramen ovale (PFO) is a remnant of the fetal circulation. Multiple studies suggest that migraine is more prevalent in subjects with PFO and vice versa. It is unclear if there is a causal relationship or simply a co-existence of these two conditions. Furthermore, the treatment of migraine with percutaneous closure PFO remains controversial. Methods: We reviewed studies pertaining to the relationship between PFO and migraine as well as the effects of treatments on migraine attacks. Results: We briefly summarized potential pathophysiological mechanisms of migraine, and elaborated on migraine type, frequency, and clinical symptoms of migraine with PFO and the clinical features of PFO with migraine. We also addressed the effects of PFO closure on migraine attacks. Conclusion: The evidence supports a “dose-response” relationship between migraine and PFO although more work needs to be done in terms of patient selection as well as the inclusion of an antiplatelet control group for PFO closure interventions to uncover possible beneficial results in clinical trials.